Effect of Trichoderma and fungicide on seedling establishment and yield performance of dry direct seeded boro rice - Hassan, MM; Hossain, S; Rahman, MM; Mahmud, S (Journal of the Bangladesh Agricultural University, 2016)
Poor seedling establishment and seedling mortality is the major barrier to optimum stand establishment in dry direct seeded boro rice. Experiments were carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh, Bangladesh during January to June 2013 to study the effect of Trichoderma and fungicide application on seedling establishment and yield performance of dry direct seeded Boro rice. The experiment comprised ten treatment combinations of Trichoderma and fungicides viz. seed treatment with Trichoderma (M1), seed treatment with Trichoderma+spraying of Thiovit (M2), seed treatment with Trichoderma + spraying of Propiconazole (M3), seed treatment with Trichoderma + spraying of Thiovit and Propiconazole (M4), spraying of Thiovit (M5), spraying of Propiconazole (M6), seed treatment with Thiovit + spraying of Propiconazole (M7), seed treatment with Propiconazole + spraying of Thiovit (M8), spraying of mixture of Thiovit and Propiconazole (M9), and control (no fungicide or Trichoderma ) (M10).The experiments used Randomized Complete Block Design (RCBD) with three replications. Experiment revealed that seed treatment with Trichoderma harzianum followed by spraying of Thiovit gave the highest yield of rice. The study concludes that Trichoderma and then application of sulphur fungicide at 20 days after sowing could be practiced for ensuring high seedling establishment and yield of rice under dry direct seeded system in boro season. J. Bangladesh Agril. Univ. 14(1): 37-42, June 2016